Medicplast - a novel and green biodegradable medical plastic bag - Noor Wirda Aryanie, Mohd Zaki; Rohani, Arbain; Sam, Sung Ting, Dr.; Nik Noriman, Zulkepli, Dr. (Macao Innovation & Invention Association, 2013)
The team has won silver medal at Macau International Innovation & Invention Expo 2012, 29th June - 1st July 2012 was held at Macau Fisherman Wharf Exhibition Centre Macau, China.